HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN RAWAT INAP DI RSUD KABANJAHE KABUPATEN KARO TAHUN 2019 - Efrata Sembiring; Rifai Siregar; Novrika Silalahi (Jurnal Penelitian Kesmasy, 2019)
The Relationship between Service Quality and Inpatient Satisfaction at Kabanjahe Hospital Kab. Karo in 2019. Thesis, Department of Public Health, Faculty of Public Health, Deli Husada Deli Tua Health Institute. (Supervised by Ns. Megawati Sinambela, S.Kep.,M.Kes) Background: The hospital is a complete and complex health service center. Hospitals are very close to human life so that wherever they are located, hospitals are almost never empty. According to Article 1 of Law Number 14 of 2009, a hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient and emergency services. This study aims to determine that there is a relationship between service quality and inpatient satisfaction. at Kabanjahe Hospital, Kab. Karo of 2019. Methods: This type of research is using a quantitative research design, so the research uses a cross sectional approach, which is a study to study the dynamics of the correlation between the independent variable and the dependent variable by means of an observation approach or data collection at once (point time approach). .. The sampling technique is accidental sampling, which is done by taking cases or respondents who happen to exist or are available in a place according to the research context. Where the sample in this study were 80 people. Data collection techniques using questionnaire sheets and respondent observation sheets. The data analysis technique used Chi-Square. Results: a significant relationship with the dependent variable, namely patient satisfaction, obtained by respondents who answered quite well as many as 54, the highest among all variables with p = 0.000 and , it was stated that there was a significant relationship between the relationship between health service quality and patient satisfaction at Kabanjahe Hospital Kab. Karo of 2019. Conclusion: This study means that there is a significant relationship between the relationship between the quality of health services and patient satisfaction at Kabanjahe Hospital Kab. Karo of 2019.